Cómo se imagina la computación en la ciencia ficción centroamericana: lectura etnocrítica de cuatro relatos - Munguía Molina, Diego (2025)
An analysis of science fiction works written by Central American authors was conducted with the question: How have the authors of Central American science fiction from the late 20th and early 21st centuries imagined the relationship between the peoples of our region and computing? Four stories published between 1966 and 2011 by Alfredo Cardona Peña, Hugo Lindo, Julio Calvo Drago, and Evelyn Ugalde Barrantes were considered. Using the ethnocritical reading methodology, both the context and the discursive structure of each work are analyzed from an intersectional approach and the perspective of the other— within the framework of colonial power relations. It was determined that in the imagined worlds of these stories, the colonial center/periphery dependency is not overcome, and the possibility of a native construction of technology, tailored to the needs of our region’s communities, is not envisioned.